SLIPS OF THE EARS ON PHONETIC KNOWLEDGE TOWARD SURABAYA INDIE ROCK MUSIC SINGER - SETIYAWAN, ARIS (Language Horizon: Journal of Language Studies, 2014)
SLIPS OF THE EARS ON PHONETIC KNOWLEDGE TOWARD SURABAYA INDIE ROCK MUSIC SINGER Aris Setiyawan English Literature, Faculty of Languages and Arts, Surabaya State University arisemenster@gmail.com Widyastuti, S.S., M.Pd. English Department, Faculty of Languages and Arts, Surabaya State University wid_unesa@yahoo.com ABSTRACT In learning the lyric from song, often times rockers get misperceived some words when singing the song. In this case, misperceived words are the process of a deviation between the actual state of information and the perceived state when obtaining information from listeners surrounding source information. This problem leads rocker having slips of the ears. Rockers report hearing, as clearly and as distinctly as any correctly perceived stretch of speech which is something that does not correspond to the speaker’s actual utterance. This research brings slips of the ears on phonetic and lexical knowledge which is concern with knowledge and recognizing ability in phonetic sound and mental lexicon as the phenomena occurred in rockers perception. It takes 3 major problems in phonetic knowledge within its analyses. The research problems proposed are (1) what consonant misperception, (2) vowel misperception, and (3) segment order misperceptions are produced by rockers in understanding song lyric. This research is descriptive-qualitative research and using 4 rockers around and in Surabaya. The data are taken from the rocker utterances when listening ‘It’s My Life’ song. Based on the findings, some facts are revealed such as there are 5 misperceptions involving consonant which voicing and place of articulation are as the dominant factor and 1 misperception in vowel involving height as the dominant factor. Segment order has 6 misperceptions in all 3 types of misordering which is word boundaries as the dominant misperception. Moreover, it also finds that song segments particularly intro, refrain, and bridge gives different influence toward misperception produced by the rockers Key words: Misperception, Slips of the Ears, Phonetic Knowledge ABSTRAK Dalam pembelajaran lirik dari lagu, seringkali roker salah mempreseprikan beberapa kata ketika menyanyikan lagu. Ini merupakan masalah dari proses dari sebuah penyimpangan antara informasi aktual dan yang dipresepsikan ketika mendapatkan informasi dari sumber informasi disekitar perndengar. Masalah ini membawa roker terhadap terjadinya fenomena keliru dengar. Dalam permasalahan ini roker mendengar sejelas dan senyata presepsi benar dari ucapan, yang mana sesuatu yang tidak ada kaitannya dengan ucapan aktual pembicara. Penelitian ini mengambil fenomena keliru dengar pada ilmu fonetik yang berkaitan dengan ilmu dan kemampuan mengenal bunyi fonetik sebagai fenomena yang terjadi dalam presepsi rocker. Penelitian ini mengambil 3 masalah utama pada ilmu fonetik dalam analisisnya. Rumusan masalah yang diajukan adalah (1) salah persepsi konsonan (2) huruf vokal (3) dan urutan segmen salah persepsi apa yang di produksi oleh rocker dalam memahami lirik lagu. Penelitian ini menggunakan penelitian deskripsi-kualitatif dan menggunakan 4 rocker sekitar dan di Surabaya. Data diambil dari ucapan rocker ketika mendengarkan musik ‘It’s My Life’. Berdasarkan temuan-temuan, beberapa fakta ditemukan seperti ada 5 salah presepsi melibatkan konsonan yang suara dan tempat artikulasi sebagai faktor dominan dan 1 salah persepsi pada huruf vokal yang melibatkan tingginya letak lidah sebagai faktor dominan. Urutan segmen mempunyai 6 salah presepsi dalam 3 macam salah penempatan yang mana kelompok kata sebagai faktor dominan. Lebih lanjutnya, penelitian ini menemukan bagian - bagian lagu seperti intro, refrain, dan bridge memberikan pengaruh berbeda terhadap salah dengar yang diproduksi oleh rocker. Kata kunci: salah presepsi, keliru dengar, pengetahuan fonetik INTRODUCTION Misperception occurs when the song that heard by singer is in fast spoken or not clear enough, as stated by Pisoni et al, in a portion of errors a listener (singer) misperceives a single segment (Pisoni et al, 2005). According to Blevins & Garrett, 1998 and Ohala, 1990 In The Handbook of Speech Perception, misperception is occurred by the sound change. The limitations of perceptually-ranked faithfulness constraints are shared by some theories that locate perceptual constraints in the process of sound change rather than in synchronic grammars. Then it is also influenced by second language, studies in second language learning have found that listeners are more adept at perceiving sounds of their native language than those of a second language acquired later in life e.g. Polka and Werker (1994) and Dupoux et al. (1997). This misperception makes singer utterance in the form of sentence or word will not deliver properly as speaker’s utterance in the song because it is the matter of slips of the ears Slips of the ears can be classified into 5 areas Bond in Pisoni (2005). They are slips of the ears in phonetic knowledge, phonological knowledge, lexical knowledge, Syntax, and Semantic and Pragmatic. Slips of the ears occurred in singer perception is unconsciously uttered by singer (e.g. It’s like a math problem -> mouth problem). The research will be focused on how slips of the ears occur on phonetic knowledge in consonant, vowel, and segment order misperception. Several theories are applied in conducting this study. The first theory is misperception theory comes by Akashi and Arita. In very general terms misperception is process of deviation between actual meaning and perceived state when obtaining information (Akashi and Arita, 2002). Misperception can be classified into two categories depending on information sources. They are direct misperception and indirect misperception. Misperception which occurs when each individual obtains firsthand information from passive and certified sources (e.g. environment) is called direct misperception. On the other hand, misperception which occurs when each individual obtains indirect information from active and not certified sources (e.g. other agents) is called indirect misperception (Akashi and Arita, 2002). Another theory used in this study is from Bond. In this case, the theory is referring to slips of the ears area which are on phonetic knowledge. In a portion of errors a listener misperceives a single segment so that speaker’s utterance and listener’s utterance differ in only one segment. In this case, consonants have much more misperceived frequently than vowel. It is because misperceptions that are produced by listeners belonging to misperception of single segment (Pisoni, et al. 2005:291). Bond’s theory is supported by 2 theories which are delivered by Yule and Odden. Three labels of phonemes is theory from Yule labeling the consonants and vowel descriptions from Odden describing the vowels. RESEARCH METHOD Descriptive qualitative is the method used in this research. 4 rockers are used around and in Surabaya. Rockers are categorized as indie music singer. The source of data is taken from ‘It’s My Life’ which is popularized by Bon Jovi. Meanwhile the data used in this research is rocker utterances. Field research is applied to find out the misperception produced by the rockers. In this study, the writer is the key instrument who collects rocker utterances. The writer uses his skill to collect the data from various sources. Laptop, mobile phones and earphone are used as the tools to support the instruments and data in conducting this study. In conducting data analysis in his research study the researcher uses some procedures and techniques. The writer collects the data by preparing the edited song of ‘It’s My Life’ and recording the rocker utterances. In order to answer the three research questions, some techniques are applied in conducting the data. There are 4 steps in analyzing the data: 1. Finding the slips of the ears The researcher finds out the utterance categorized as slips of the ears occurred in subject’s utterance. The slips of the ears will be bold marked to the words in utterance. 2. Identifying the slips of the ears based on phonetic knowledge The researcher identifies the words in subject’s utterance that are categorized as slip of the ears based on classification theory of phonetic knowledge. 3. Identifying the slips of the ears based on song’s segments The researcher identifies the words in subject’s utterance that are categorized as slip of the ears based on song’s segment which they are intro, refrain, and bridge. 4. Explaining the data After finding and identifying the slip of the ears in subject’s utterance, the researcher gives explanation of each word that has been found. The Analysis of the study are based on the three research questions: The first and second research question is about misperception in consonant and vowel misperception. The first step of answering the first research question is analyzing consonant and vowel by three labels of phonemes and vowel descriptions. Consonant misperception is analyzed by 3 aspects in consonant labeling particularly voicing, place of articulation, and manner of articulation. Vowel misperception is analyzed by 4 aspects in vowel descriptions particularly height, backness, roundness, and vowel length. The third research question is about misperception in segment order. In this case, the question is answered by using misordering types in segment order misperception particularly misperceived in word boundaries, cross syllable, and within a syllable. FINDINGS AND DISCUSSION There are several misperceptions produced by rockers when singing ‘It’s my life’. Those misperceptions fulfill all areas in phonetic knowledge through consonant, vowel, and segment order. In phonetic knowledge, consonant has dominant misperception than vowel which 5 misperceptions in consonant and 1 misperception in vowel. In segment order, 3 types of misordering are produced by rocker. Misordering in word boundaries are the common misperception occurred. Common cases that found in consonant and vowel misperception Based on findings, rockers had some difficulties perceiving consonant and vowel. It can be seen from 5 consonant misperceptions produced in intro and refrain segment and 1 vowel in second intro as in Table 1. There are 3 aspects in consonant that influence misperception by rockers. They are voicing, place of articulation, and manner of articulation (Yule, 2010). And 4 aspects in describing vowel, they are height, backness and roundness and vowel length (Odden, 2005). Table 1 Consonant and vowel misperceptions No Original Utterance Subject utterance 1 I ain’t gonna be just a face in the crowd [?g??.n?] I donna be for the present crowd [?d??.n?] 2 This is for the ones who stood their ground [gra?nd] This is for wrong with spoktit crown [kra?n] 3 I ain’t gonna be just a face in the crowd [kra?d] I don’t wanna live dut the shake me doubt [da?t] 4 You’re gonna hear my voice [h?r] You gonna hit my voice [h?t] 5 I just want to live while I’m alive [d??st] I yust gonna live when im alive [j?st] 6 Got to make your own breaks [j?? r] ..make you own break [ju?] Consonant /g/ had misperceived into consonant /d/ which replaced the word ‘gonna’ [?g??.n?] to be ‘donna’ [?d??.n?] in first intro. There was replacement of the consonant /g/ to the consonant /d/ which occured on the initial segment of the word. Those consonants can be found its characteristic by using labeling like consonant /g/ has label as voiced, velar, stop meanwhile consonant /d/ has label as voiced, alveolar, and stop. Therefore this misperception can be mentioned as misperception in place of articulation because it occurs in place of articulation area specifically on velar and alveolar. Consonant /g/ in ‘ground’ [gra?nd] was replaced by consonant /k/ in ‘crown’ [kra?n] in second intro. Related to consonant labeling, consonants /g/ has label as voiced, velar, and stop, while consonant /k/ has label as voiceless, velar, stop, so that it can be seen the different between those consonants are located on voicing. And also this misperception can also be mentioned as misperceived as another stop because these consonants have the same manner of articulation in stop. Consonant /k/ was replaced to consonant /d/ in first intro which both consonants had different characteristics. As consonant /k/, it has label as voiceless, velar, and stop while consonant /d/ has label as voiced, alveolar, and stop. Therefore, it can be concluded that the distinction of them are from areas voicing (voiceless became voiced) and place of articulation (velar to be alveolar). There was also consonant reduction in subject utterance from the original utterance that was consonant /r/. Consonant /r/ in ‘hear’ [h?r] in its final consonant was replaced to word ‘hit’ [h?t] which the final consonant was /t/ in first intro. In consonant labeling, there are 2 different areas between those consonants that consonant /r/ has label as voiced, alveolar, and liquid while consonant /t/ has label as voiceless, alveolar, and stop. The different areas are in voicing (voiced becomes voiceless) and manner of articulation (liquid to stop) Consonant /d?/ was misperceived consonant /j/ in second refrain. there is distinction utterance in misperception occurs in initial segment which the words are ‘Just’ [d??st] with the initial consonant is /d?/ was misperceived to the word ‘Yust’ [j?st] which the initial consonant is /j/. The consonant labeling of those words are consonant /d?/ has label as voiced, palatal, and affricates while consonant /j/ has label as voiced, palatal, and glides. So in conclusion from the consonant labeling, the different is only on manner of articulation that is on affricates to glides. In data 6, vowel misperception occurred on word ‘your’ [j?? r] and ‘you’ [ju?] in second intro. It shows that vowel /??/ is replaced by vowel /u?/. Those vowels can be seen the distinction by describing vowel category, vowel /??/ describes as middle back rounded while vowel /u?/ describes as high back rounded. Therefore, both vowels have distinction only on vowel height (middle and high). Otherwise, both vowels also have the same characteristic in one way that both vowels are categorized as tense vowel. This is in line with Bond that in portion of errors a listener misperceives a single segment. Consonants have much more misperceived frequently than vowel. It is because misperceptions that are produced by listeners belonging to misperception of single segment (Bond in Pisoni et.al, 2005). It shows that in consonant misperception voicing and place of articulation area influence more toward rocker’s perception. In voicing, misperception produced by changing voiced to voiceless. It can be seen that there are 3 from 5 misperceptions in data 2 to 4. In place of articulation, misperceptions are produced around alveolar to velar as in data 1, 3, and 4. And there is only one misperception involving vowel which is height as the case in rocker utterance. It can be assumed that this segment has less attention from the rockers when they are singing so they have some misperceptions. Common cases which are found in segment order misperception Based on findings, segment order misperceptions were also occurred in rocker’s utterances. It can be seen in findings that there are 6 misperceptions categorized as misperception in segment order. There are 3 types of segment order misperception in this case, they are misordering in word boundaries, miordering cross syllable, and misordering within a syllable (Pisoni et.al, 2005). All misperceptions will be displayed as in Table 2 Table 2 Segment order misperception No Original Utterance Subject utterance 1 No silent prayer for the faith departed Silence pray for fifty parted 2 No silent prayer for the faith departed Wee baby for fitty body 3 No silent prayer for the faith departed Silent pray for fifty parrit 4 Tomorrow’s getting harder make no mistake Tommorow’s being hard min moment stay 5 Tomorrow’s getting harder make no mistake Tomorrow getting hard for minsday 6 Tomorrow’s getting harder make no mistake Tommorow?s being hard min moment stay In first utterance of ‘faith departed’, the way to pronounce the word utters in single pronunciation. It occurred in first intro. The misperception can be seen on the gliding between those two words such as in utterance ‘fifty parted’. In this utterance, gliding between the words occur like in original utterance ‘faith di-’ pronounces as [fe?θd?-] is blended to be ‘fifty’ [?f?f.ti]. It indicates that utterance ‘faith di-’ is pronounced as a single word in ‘fifty’. The last segment of subject utterance is uttered as the same as original utterance that is /p??r.t???d/. In second and third utterances, it occurs in the same utterance of ‘faith departed’ in first intro. Misperceptions occurred in first 2 syllables in subject utterances. However, the last segment is different from the first case for instance in utterance ‘fifty body’ pronounced as [?f?f.tib??.di] with replacement of consonant /p/ to consonant /b/ in middle segment and ‘fifty parrit’ pronounced as [?f?f.tip??r.???t] with replacement consonant /d/ to consonant /t/in the last segment. Utterance ‘no mistake’ [no? m??ste?k] which uttered ‘no? m?? became uttered in single word as ‘?mo.m?n’ in second intro. It indicates that subject utterance have blended in first syllable of word ‘mistake’ to become one single word of ‘momen’. The last syllable of that word has formed to another word. That is stay or [ste?]. In utterance 4.1.9 shows that rocker utterance ‘no mistake’ got misperceived to another utterance which there was gliding segment between two words and made a misperception in word boundaries. The word ‘mistake’ in second intro was replaced to word ‘minsday’ which was actually meaningless. Cross syllable in those words can be seen particularly in syllable [m?] in mistake and [m?ns] in minsday. From that phonetic transcription, it can be concluded that cross syllable had occurred because consonant /n/ and /s/ which are actually located on second syllable, was moved to first syllable and it formed new syllable in in rocker’s utterance. Misordering segment occurred on word ‘getting’ was in first syllable in second intro. It can be seen by the segment replacement of the first syllable of word ‘getting’ [get] is replaced to another syllable of word ‘being’ [bi?]. The last syllable is uttered same in both words [??]. In Table 2 shows that segment order in word boundaries have many cases of all misperceptions. It can be seen that there are 3 of 5 misperceptions which occur in word boundaries. All word boundaries misperception have the same cases which is gliding segment between two words in single utterance. It blends with the first syllable in second word. The rest types of segment order have the same number for instance there is one in cross syllable and within a syllable. In cross syllable, misordering occurred in crossing last syllable in one word. Misordering within a syllable occurred with replacement in last syllable in one word. Based on findings all misperceptions that were found in rocker’s utterance are categorized as direct misperception. As Akaishi and Arita said that direct misperception occurs when individual or in this case is the rocker, obtain firsthand information or source which comes from hearing the song direct from earphone which is the rightness of sources (original source) is assured (Akaishi and Arita, 2002). CONCLUSION Consonant and vowel influences rocker’s perception through consonant misperception occurred in rocker’s perception by 5 misperceptions occurred in the song particularly consonant /g/, /r/, /k/ and /d?/ with voicing and place of articulation are dominant factors. Only 1 vowel misperception produced by rocker that is vowel /??/ with the height as the misperceived factor. Segment order had misperceived 6 misperceptions which are misordering in word boundaries, cross syllable, and within a syllable. The dominant factor in segment order is gliding segment in word boundaries misordering and other factors are crossing last syllable and replacement in last syllable. Since this research is limited to rockers and phonological approaches, so the writer suggests for the next researcher, especially linguistic researcher. It can also be taken to other aspects like in lexical knowledge, phonological knowledge, syntax, or semantic and pragmatic. It will make other varieties in conducting the analysis by the next researcher. And also this research can also be used to another subject as in education (finding on what areas that student get problem in listening). For the rockers and singer, rockers have some misperceptions based on their phonetic knowledge when they are listening and singing a song. It is important to know what areas in phonetic and lexical knowledge (consonant and vowel, segment order, and content and function word) and the song segments like intro that should be more aware in learning a song to avoid more misperceptions when they are singing in front of the public. REFERENCES Akaishi, Jin, and Takaya Arita. (2002). Misperception, Communication and Diversity. Bond, Z. S. (1999). Slips of the Ear: Errors in the Perception of Casual Conversation. San Diego, CA: Academic Press. Fromkin, Victoria, Robert Rodman, and Nina Hyams. (2011). 9 ed. An Introduction to Language. Wadsworth: Cengage Learning Odden, David. (2005). Introducing Phonology. New York: Cambrigde University Press. Pisoni, David B., and Robert E. Remez. (2005). The Handbook of Speech Perception. Cornwall: Blackwell Publishing Yule, George. (2010). The Study of Language 4 ed. New York: Cambridge University Press